Laparoscopic proximal gastrectomy with double‐flap technique versus laparoscopic subtotal gastrectomy for proximal early gastric cancer. Issue 2 (12th December 2019) - Kano, Y.; Ohashi, M.; Ida, S.; Kumagai, K.; Sano, T.; Hiki, N.; Nunobe, S.
Abstract : Background: Laparoscopic proximal gastrectomy with double‐flap technique (LPG‐DFT) and laparoscopic subtotal gastrectomy (LSTG) may replace laparoscopic total gastrectomy (LTG) for proximal early gastric cancer. The aim of this study was to evaluate short‐ and long‐term outcomes after LPG‐DFT and LSTG. Methods: Patients who underwent LPG‐DFT or LSTG at the Cancer Institute Hospital in Tokyo between January 2006 and April 2015 were included in this retrospective study. Operative procedures were selected based on the distance from the cardia to the proximal boundary of the tumour, tumour location and predicted remnant stomach volume. Patient characteristics, surgical data, markers of postoperative nutritional status, such as blood chemistry and bodyweight loss, and endoscopic findings were compared between procedures. The main study outcome was nutritional status. Results: A total of 161 patients (LPG‐DFT 51, LSTG 110) were included. Types of postoperative complication occurring more than 30 days after surgery differed between the two procedures. Remnant stomach ulcers, including anastomotic ulcers, were observed only after LPG‐DFT, whereas complications involving the small intestine, such as internal hernia or small bowel obstruction, occurred more frequently after LSTG. Values for total protein, albumin, prealbumin and bodyweight loss were comparable between the two procedures at 36 months after surgery. Haemoglobin concentrations were higher after LPG‐DFT than after LSTG at 24 months (13·4 versus 12·8 g/dl respectively; P  = 0·045) and 36 months (13·5 versus 12·8 g/dl; P  = 0·007) after surgery. The rate of Los Angeles grade B or more severe reflux oesophagitis was comparable. Conclusion: LPG‐DFT and LSTG for proximal early gastric cancer have similar outcomes, but different types of complication. Abstract : Laparoscopic proximal gastrectomy with double‐flap technique is different from laparoscopic subtotal gastrectomy in terms of preventing problems involving the small intestine and anaemia after surgery for proximal early gastric cancer. However, these procedures are comparable for other outcomes, even though they are opposing procedures. 'Opposite techniques but both applicable' Abstract : Antecedentes: La gastrectomía proximal laparoscópica con técnica de doble derivación ( double flap technique, LPG‐DFT) y la gastrectomía subtotal laparoscópica ( laparoscopic subtotal gastrectomy, LsTG) pueden sustituir a la gastrectomía total laparoscópica (laparoscopic total gastrectomy, LTG) para el cáncer gástrico precoz ( early gastric cancer, EGC) proximal. El objetivo de este estudio fue evaluar los resultados a corto y a largo plazo tras LPG‐DFT y LsTG. Métodos: En este estudio retrospectivo se incluyeron pacientes que fueron sometidos a LPG‐DFT o LsTG en el Hospital del Instituto del Cáncer de Tokio entre enero 2006 y abril 2015. Las técnicas quirúrgicas se seleccionaron en base a la distancia entre el cardias y el borde proximal del tumor, localización del tumor, y el volumen previsto del remanente gástrico. Las características de los pacientes, datos quirúrgicos, marcadores del estado nutricional postoperatorio, tales como la bioquímica sanguínea y la pérdida de peso corporal ( body weight loss, BWL), y los hallazgos endoscópicos se compararon entre las técnicas. El resultado principal del estudio fue el estado nutricional. Resultados: Se incluyeron un total de 161 pacientes (LPG‐DFT 51, LsTG 110). Los tipos de complicaciones postoperatorias que aparecieron a más de 30 días después de la cirugía variaron entre ambas técnicas. Las úlceras en el remanente gástrico, incluyendo úlceras anastomóticas, solo se observaron tras una LPG‐DFT, mientras las complicaciones relacionadas con el intestino delgado, como la hernia interna o la obstrucción de intestino delgado, sucedió con más frecuencia tras una LsTG. Los valores de proteínas totales, albúmina, prealbúmina, y BWL fueron comparables entre ambas técnicas a los 36 meses después de la cirugía. Las concentraciones de hemoglobina fueron más altas tras una LPG‐DFT que tras una LsTG a los 24 (13, 4 versus 12, 8 mg/dL, P = 0, 045) y 36 meses (13, 5 versus 12, 8 mg/mL, P = 0, 007) después de la cirugía. Las incidencias de esofagitis por reflujo grado B Los Angeles o más grave fueron comparables. Conclusión: La LPG‐DFT y la LsTG para el EGC proximal presentan resultados bastante similares, pero difieren en el tipo de complicaciones.